Cryptocurrency Investment: Financial Technology Policy, Financial Literacy and Expected Return - Irfan irfan (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study aims to analyze the influence of financial technology, financial literacy, and expected returns on cryptocurrency investment interest among Sun Plaza Medan employees. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to Sun Plaza Medan tenant employees who met the research criteria. The sample size in this study was 89 respondents. The data analysis technique used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that financial technology has a positive and significant effect on cryptocurrency investment interest, financial literacy has no effect on cryptocurrency investment interest, and expected returns have no effect on cryptocurrency investment interest among Sun Plaza Medan employees. These findings indicate that easy access to financial technology, adequate financial understanding, and perceptions of potential investment profits are important factors in shaping individual interest in investing in crypto assets.